Poisson’s Ratio and Young’s Modulus of Lipid Bilayers in Different Phases - Jadidi, Tayebeh; Seyyed-Allaei, Hamid; Tabar, M. Reza Rahimi; Mashaghi, Alireza (Frontiers in Bioengineering and Biotechnology, 2014)
A general computational method is introduced to estimate the Poisson's ratio for membranes with small thickness. In this method, the Poisson's ratio is calculated by utilizing a rescaling of inter-particle distances in one lateral direction under periodic boundary conditions. As an example for the coarse grained lipid model introduced by Lenz and Schmid, we calculate the Poisson's ratio in the gel, fluid, and interdigitated phases. Having the Poisson's ratio, enable us to obtain the Young's modulus for the membranes in different phases. The approach may be applied to other membranes such as graphene and tethered membranes in order to predict the temperature dependence of its Poisson's ratio and Young's modulus.